Efektivitas Pupuk Organik Granul Diperkaya Mikoriza dan Lamtoro terhadap Pertumbuhan dan Produksi Sorghum bicolor Varietas Samurai 1: Effectiveness of Granular Organic Fertilizer Enriched with Mycorrhiza and Lamtoro on Growth and Production of Sorghum bicolor Variety Samurai 1 - Prischa Dewi, Andini; Karti, Panca Dewi Manu Hara; Prihantoro, Iwan (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
This study aimed to evaluate the effectiveness of granular organic fertilizer enriched with mycorrhiza and Lamtoro on the growth and production of Samurai 1 sorghum. The experiment employed a randomized block design (RBD) with four treatments: without fertilizer application (B0), bokashi (B1), bokashi + mycorrhiza (B2), bokashi + mycorrhiza + Lamtoro (B3), at a dose of 4 tons ha⁻¹ with four replications. Analysis of variance (ANOVA) results showed that organic fertilizer treatments had a significant effect (p<0.05) on growth and yield, but no significant effect on sugar content. Further tests indicated that B3 differed significantly from B0, B1, and B2 in terms of growth and yield parameters. It can be concluded that the combination of bokashi, mycorrhiza, and Lamtoro (B3) is the most effective treatment in enhancing the growth and yield of Samurai 1 sorghum Keywords: lamtoro, granulated organic fertilizer, mycorrhiza, plant growth and production, sorghum